PENGEMBANGAN MEDIA PERMAINAN ULAR TANGGA UNTUK MENINGKATKAN PERENCANAAN KARIER SISWA - Zahra, Eza Fatiha; Nurmala, Meilla Dwi; Wahyuningsih, Lenny (Institut Daarul Qur'an Jakarta, Indonesia, 2025)
The research was motivated by the phenomenon of low career planning in vocational students. Based on preliminary studies conducted on class XI students of SMKS IKPI Labuan, the results showed that 14 students (19%) were in the high category, 40 students (54%) were in the medium category, and 20 students (27%) were in the low category. This study aims to determine whether the career snakes and ladders game media developed as learning media is able to provide an understanding of careers so that it can improve students' career planning process. The method used in this research is Research & Development (R&D) with the 4D model, which includes define, design, development and dissemination. The subjects in this study were 11th grade students of SMKS IKPI Labuan. Data collection techniques in this study were questionnaires and literature studies. In its development, evaluation is carried out to see the feasibility of the product. The evaluation was carried out by media and material experts, linguists and practitioners. The results showed that the feasibility of products from media and material experts obtained a score of 78.33% (feasible), the feasibility of products from linguists was 85.71% (very feasible), and practitioners were 97.91% (very feasible). So that the average value of all assessments is 87.31% in the “Very Feasible” category for use. So, it can be concluded that the snakes and ladders game media can be used as a supporting tool in guidance and counseling services, especially to help understand and plan the careers of class XI students of SMKS IKPI Labuan.